List of Trade Unionists & Labour Party Members [International Brigade]
1937 034-0192-013 11. ADDITIONAL LIST OF TRADE UNION OF LABOUR PARTY MEMBERS. J. Angus Guild of Insurance Officials London Br. Dependant: W. Bradshaw Opst. Office Engineers North East Section Dependant: *D. Bennett Amalgamated Moulders; also Co-op Party Walsall Dependant: N. Baxter Boot and Shoe Workers Leeds No.2 Dependant: H. Cowdray Boilermakers No.7 Birkenhead Dependant: Mrs. H. Cowdray, 23 Cleveland St., Birkenhead. (£1-15-0) E. Edney TGWU 1/553 Camberwell Dependant: E. Ellis Shop Assits. Dist. Coun. Dist. Col. Nac Chemists Section. Dependant: *W. Faulkener AEU Hull, also L.P. Hull Dependant: O. Green Typographical Assoc. B'ham. Dependant: D. Gillan Jute & Textile Workers, Dundee Dependant: Mrs. Gillan, 19 Hepburn St., Dundee (£1-0-0) *A. Holmes Labour Party Everton - Vice-Chairman. Dependant: Mrs. A. Holmes, c/o J.J. Coward, 52 Laurel Rd., Fairfield, Liverpool (£1-10-0) H. Hammond Woodworkers S.E. London Dependant: G.Hornsby NUGMW Derby TC Delegate Derby Co-op Executive. Dependant: Mrs. Hornsby, 61 Malcolm St., Derby (£1-10-0) J. Jolly Nelson Weavers Union Dependant: Mrs. Jolly, 47 Thorne St., Burnley (£1-0-0) W. Jacobson RCA Del. & Cte. Also Edmonton Co-op Pol Council. Dependant: H. Keegan Lanarkshire Miners Union - Shettleston Branch Dependant: Mrs. Keegan, 116 Bredesholm Rd., Baillieston, Glasgow. (£1-0-0) W. McGuire Shop Assts. Dundee Branch Dependant: 292/946/34/193(xi)